2007
DOI: 10.1126/science.1144090
|View full text |Cite
|
Sign up to set email alerts
|

Increased Wnt Signaling During Aging Alters Muscle Stem Cell Fate and Increases Fibrosis

Abstract: The regenerative potential of skeletal muscle declines with age, and this impairment is associated with an increase in tissue fibrosis. We show that muscle stem cells (satellite cells) from aged mice tend to convert from a myogenic to a fibrogenic lineage as they begin to proliferate and that this conversion is mediated by factors in the systemic environment of the old animals. We also show that this lineage conversion is associated with an activation of the canonical Wnt signaling pathway in aged myogenic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

59
1,337
7
12

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,338 publications
(1,415 citation statements)
references
References 17 publications
59
1,337
7
12
Order By: Relevance
“…In line with previous studies (Bernet et al, 2014; Brack et al, 2007; Chakkalakal, Jones, Basson, & Brack, 2012; Conboy, Conboy, Smythe, & Rando, 2003; Cosgrove et al, 2014; Lee et al, 2013; Shavlakadze, McGeachie, & Grounds, 2010; Sousa‐Victor et al, 2014), we found that muscle regeneration after cardiotoxin (CTX) injury is delayed in male aged animals (Figure 1a–c), as shown by the distribution of the cross‐sectional area (CSA; Supporting information Figure S1A–D), the mean CSA (Figure 1b), the increase in necrotic fiber content at Day 8 post‐CTX (Figure 1c), and the muscle mass alterations during the regeneration process (Figure 1d).…”
Section: Introduction Results Discussionsupporting
confidence: 92%
“…In line with previous studies (Bernet et al, 2014; Brack et al, 2007; Chakkalakal, Jones, Basson, & Brack, 2012; Conboy, Conboy, Smythe, & Rando, 2003; Cosgrove et al, 2014; Lee et al, 2013; Shavlakadze, McGeachie, & Grounds, 2010; Sousa‐Victor et al, 2014), we found that muscle regeneration after cardiotoxin (CTX) injury is delayed in male aged animals (Figure 1a–c), as shown by the distribution of the cross‐sectional area (CSA; Supporting information Figure S1A–D), the mean CSA (Figure 1b), the increase in necrotic fiber content at Day 8 post‐CTX (Figure 1c), and the muscle mass alterations during the regeneration process (Figure 1d).…”
Section: Introduction Results Discussionsupporting
confidence: 92%
“…[5][6][7] Conversely, both dystrophic and aged skeletal muscle display activated WNT signaling resulting in increased muscle fibrosis. 8 In DMD, a similar dysregulation of the transcriptional-level WNT signaling components has been reported. 9 MicroRNAs (miRNAs) have been shown to have an essential role in muscle development, differentiation, and disease.…”
supporting
confidence: 54%
“…However, in the case of aged muscle, the regenerative cascade is characterized by a shift from functional myofiber repair toward increased extracellular matrix (ECM) deposition (Carlson, 1995; Grounds, 1998). This impaired regeneration, among other things, appears to be attributed to dysfunction in MuSC proliferative capacity (Conboy et al ., 2003) and MuSC divergence toward a fibrogenic lineage (Brack et al ., 2007). …”
Section: Introductionmentioning
confidence: 99%
“…in vitro systems have confirmed the exquisite sensitivity of stem cells to extrinsic mechanical and structural cues emanating from the surrounding microenvironment (Engler et al ., 2006; Gilbert et al ., 2010). In vivo studies investigating modulation of the microenvironment have similarly demonstrated effects on the proliferation, migration, and myogenicity of both endogenous (Conboy et al ., 2005; Brack et al ., 2007) and transplanted MuSCs (Palermo et al ., 2005; Gargioli et al ., 2008; Ambrosio et al ., 2009, 2010; Distefano et al ., 2013), effects that ultimately affect muscle regeneration and function (Ambrosio et al ., 2009; Distefano et al ., 2013). Still, little is known about how aging affects properties of the skeletal muscle ECM and how such alterations may affect MuSC fate.…”
Section: Introductionmentioning
confidence: 99%